Whole and fractionated yellow pea flours reduce fasting insulin and insulin resistance in hypercholesterolaemic and overweight human subjects - Marinangeli, Christopher P. F.; Jones, Peter J. H. (British journal of nutrition, 2011)
The objective of the present study was to compare whole pea flour (WPF) to fractionated pea flour (FPF; hulls only) for their ability to reduce risk factors associated with CVD and diabetes in overweight hypercholesterolaemic individuals. Using a cross-over design, twenty-three hypercholesterolaemic overweight men and women received two-treatment muffins/d containing WPF, FPF or white wheat flour (WF) for 28 d, followed by 28 d washout periods. Daily doses of WPF and FPF complied with the United States Department of Agriculture's recommended level of intake of half a cup of pulses/d (approximately 50 g/d). Dietary energy requirements were calculated for each study subject, and volunteers were only permitted to eat food supplied by the study personnel. Fasting insulin, body composition, urinary enterolactone levels, postprandial glucose response, as well as fasting lipid and glucose concentrations, were assessed at the beginning and at the end of each treatment. Insulin concentrations for WPF (37·8 (sem 3·4) pmol/ml, P = 0·021) and FPF (40·5 (sem 3·4) pmol/ml, P = 0·037) were lower compared with WF (50·7 (sem 3·4) pmol/ml). Insulin homeostasis modelling assessment showed that consumption of WPF and FPF decreased (P < 0·05) estimates of insulin resistance (IR) compared with WF. Android:gynoid fat ratios in women participants were lower (P = 0·027) in the WPF (1·01 (sem 0·01) group compared with the WF group (1·06 (sem 0·01). Urinary enterolactone levels tended to be higher (P = 0·087) in WPF compared with WF. Neither treatment altered circulating fasting lipids or glucose concentrations. In conclusion, under a controlled diet paradigm, a daily consumption of whole and fractionated yellow pea flours at doses equivalent to half a cup of yellow peas/d reduced IR, while WPF reduced android adiposity in women.